The Design Motif of Batik Grafika Indonesia (Batik Pusgrafin) in National Batik Diversity Through Application Subject Nirmana Dwimatra-Trimatra - Dayu Sri Herti; Dwi Riyono; Eka Triana; Immanuel Ronald David Mongkau (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2023)
This research is a continuation of the dissertation on 'Transformation of the Indonesian Graphics Center/Pusgrafin in the Renewal of Educational Media in Indonesia, 1969–2008'. As a government institution in the field of graphics, one of its tasks and functions is to develop non-formal education through graphic training throughout Indonesia. This research aims to memorize pusgrafin as a renewal of educational media through the concept of creating pusgrafin batik motifs or Indonesian graphic batik so that it can enrich the diversity of batik motifs in Indonesia. Motifs with the philosophy of graphical batik motifs from local wisdom become one of the national batik diversities and support the program to increase the creative industry in Indonesia, both in books, journals, and scientific studies. The novelty of this research is that the existence of Indonesian graphical batik motifs as the embodiment of pusgrafin as one of the media to display a new identity or characteristics of a product will be able to contribute value to regional socio-economic growth, especially in the tourism and creative industry sectors. The locus at Politeknik Negeri Media Kreatif (PoliMedia Kreatif) is one of the vocational education institutions and the only state polytechnic in DKI Jakarta Province. As a revitalization of Pusgrafin, it has a role in developing various superior products, both produced by each study program and through collaboration between study programs. This research uses an art history/historiography research method with a methodology of social science, culture, and creative industry approaches. This research uses the subject matter of Indonesian Batik Grafika motif design in advanced courses: two-dimensional nirmana and three-dimensional nirmana. The results of batik motif design in the future will be applied to fashion products, especially batik clothing and merchandise/gimmicks.